Late Fate of Cryopreserved Arterial Allografts. Issue 5 (November 2016) - Minga Lowampa, E.; Holemans, Ch.; Stiennon, L.; Van Damme, H.; Defraigne, J.O.
Abstract : Objective: Initial enthusiasm for use of cryopreserved arterial allografts was subsequently tempered by suboptimal long-term outcome. Thrombosis, anastomotic pseudo-aneurysm, allograft disruption, aneurysmal degeneration, recurrent intestinal fistulization, and persistent infection are commonly reported in series with long-term follow-up. The authors reviewed their experience over the past 15 years with the use of cryopreserved arterial allografts as a vascular substitute for vascular prosthetic infection or for primary arterial infection, to investigate allograft-related complications. Material and methods: A retrospective analysis of prospectively collected data was conducted for 103 cryopreserved arterial allografts inserted in 96 patients between July 2000 and July 2015. There were 78 patients with infected vascular prosthesis (IVP), nine patients with an aorto-enteric fistula (AEF), and nine patients with primary arterial infection (PAI). Results: The in-hospital mortality was eight out of 78 (9%) IVP patients, three out of nine AEF patients, and zero out of nine PAI patients. Median follow-up was 49 months. Allograft-related re-interventions were necessary in 29% of the patients with IVP and four of the patients with AEF, but none of the patients with PAI. Five-year survival for the IVP, AEF, and PAI patients was 53%, 44%, and 90%, respectively. Conclusion: This series highlights some shortcomings of cryopreserved arterial allografts in the long term, including suboptimal outcome-results and shortage of material. The authors discuss the allograft-related complications and suggest some tricks to minimize their risk.